Baculovirus-mediated expression, purification, and characterization of a fully activated catalytic kinase domain construct of the 70 kDa 40S ribosomal protein S6 kinase-1 αII isoform (S6K1αII) - Keshwani, Malik M. (2007)
S6K1αII is a member of the AGC subfamily of serine-threonine protein kinases, whereby catalytic activation requires dual phosphorylation of critical residues in the conserved T-loop (T229) and hydrophobic motif (HM; T389) regions of its catalytic kinase domain [S6K1αII(ΔAID); deletion of C-terminal autoinhibitory domain residues 399-502]. With regard to mimicking the synergistic effect of full dual site phosphorylation, baculovirus-mediated expression and affinity purification of the His(6)-S6K1αII(ΔAID)-T229E,T389E double mutant from Sf9 insect cells yielded enzyme with compromised activity. Higher activity preparations were generated using the Sf9 purified His(6)-S6K1αII(ΔAID)-T389E single mutant isoform, which was in vitro phosphorylated by the upstream T229 kinase, PDK1 (∼75 nmol/min/mg). Most significantly, we report that the His(6)-S6K1αII(ΔAID)-T389E construct was generated in its most highly active form (250 nmol/min/mg) by baculovirus-mediated expression and purification from Sf9 insect cells that were coinfected with recombinant baculovirus expressing the catalytic kinase domain of PDK1 [His(6)-PDK1(ΔPH)]. Approximately equal amounts of fully activated His(6)-S6K1αII(ΔAID)-T389E (5 ± 1 mg) and His(6)-PDK1(ΔPH) (8 ± 2 mg) were His(6) affinity co-purified 60 h after initial coinfection of 200 mL of Sf9 insect cells (2 × 10(6) cells/mL), which were resolved by MonoQ anion exchange chromatography. ESI-TOF mass spectrometry, MonoQ anion exchange chromatography, and kinetic assays showed His(6)-PDK1(ΔPH) to phosphorylate T229 to ∼100% after co-expression in Sf9 insect cells as compared to ∼50% under in vitro conditions, raising interest to mechanistic components not fully achieved in the in vitro reaction. Generation of fully activated S6K1 will facilitate more rigorous analysis of its structure and mechanism.